Look-Ahead Algorithm with Whole S-Curve Acceleration and Deceleration - Youdong Chen; Xudong Ji; Yong Tao; Hongxing Wei (Advances in Mechanical Engineering, 2013)
Tool paths of a complex contour machining generated by commercial CAD/CAM systems are mainly composed of many short linear/circular blocks. Though the look-ahead algorithms can improve speed and accuracy in the machining of short linear/circular segments, most of them just deal with linear segments with trapezoid acceleration and deceleration (acc/dec). In addition, the look-ahead algorithms with S-curve acc/dec are too complex to adopt the equivalent S-curve profile by approximation algorithm. To increase the smoothness of feedrate profile and machining efficiency of continuous short line and circle machining, this paper presents a feedrate profile generation approach and corresponding look-ahead algorithm with whole S-curve acc/dec. With the proposed look-ahead scheme, the feedrate profiles with S-curve acc/dec can work efficiently in a lot of short line and circle segments. Thus, the machining productivity can be increased and the feedrate profiles are smooth. The simulation and experiments verify the feasibility and validity of the proposed approach.